Peningkatan Pengetahuan Ibu Dan Status Gizi Melalui Edukasi Dan Demonstrasi Pengolahan Ikan Sebagai Alternatif Cemilan Sehat - Devia Lista; Reni Astuti; Darsin Darsin; Rusni Darmayanti; Liliati Liliati; Melyana Melyana (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Nutritional problems in toddlers remain one of the major public health issues affecting child growth and development. Limited maternal knowledge regarding balanced nutrition and low utilization of local food resources contribute to nutritional problems among children. Fish is a local food source rich in protein and essential nutrients that can be processed into healthy snacks for toddlers. Objective: This community service activity aimed to improve mothers’ knowledge and support nutritional status improvement through nutrition education and fish-processing demonstrations as an alternative healthy snack. Methods: The activity was conducted in Desa Kamelanta involving mothers with toddlers as participants. Activities included nutrition education, counseling regarding balanced nutrition and stunting prevention, as well as demonstrations of fish-based healthy snack processing. Educational media used included leaflets, direct presentations, and practical demonstrations. Evaluation was conducted through observation of participant involvement and understanding during the activity. Results: Participants showed enthusiasm during educational sessions and cooking demonstrations. Increased maternal understanding was observed regarding balanced nutrition, healthy snack selection, and utilization of local fish resources for child nutrition fulfillment. This activity also encouraged mothers to apply healthier feeding practices at home. Implication: Nutrition education combined with practical demonstrations can improve maternal knowledge and optimize the use of local food resources as an effort to improve child nutritional status and prevent stunting.